2018
DOI: 10.1177/1091581817751142
|View full text |Cite
|
Sign up to set email alerts
|

A Toxicological Assessment of Creatyl-l-Leucine

Abstract: A battery of toxicological studies was conducted to investigate the genotoxicity and repeated-dose oral toxicity of creatyl-l-leucine, a synthetic compound, in rats in accordance with internationally accepted guidelines. There was no evidence of mutagenicity in a bacterial reverse mutation test and in an in vitro mammalian chromosomal aberration test. There was no genotoxic activity observed in an in vivo mammalian micronucleus test at concentrations up to the limit dose of 2,000 mg/kg bw/d. Creatyl-l-leucine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 33 publications
(45 reference statements)
0
9
0
Order By: Relevance
“…The observation that portal venous plasma creatine concentration from CLLD rats was not different from CON rats indicates that CLL is not converted to creatine in the intestine during digestion. Unpublished data suggested creatyl-L-glutamine was only 27% hydrolyzed to creatine in an in vitro model of digestion [ 10 ]. However, we conclude CLL is not a source of creatine during digestion as there was no bioaccumulation of creatine in tissues over the 7 days of CLL supplementation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The observation that portal venous plasma creatine concentration from CLLD rats was not different from CON rats indicates that CLL is not converted to creatine in the intestine during digestion. Unpublished data suggested creatyl-L-glutamine was only 27% hydrolyzed to creatine in an in vitro model of digestion [ 10 ]. However, we conclude CLL is not a source of creatine during digestion as there was no bioaccumulation of creatine in tissues over the 7 days of CLL supplementation.…”
Section: Discussionmentioning
confidence: 99%
“…Jäger et al published an extensive analysis of potential sources of creatine and concluded that CrM was the most favorable of the compounds tested [ 9 ]. Recently it has been suggested that the molecule creatyl- l -leucine (CLL) ( Figure 1 ) may potentially serve as a bioavailable form of creatine that could be used as a dietary ingredient [ 10 ]. In the same study, it was shown that CLL had no toxicity when provided for 90 days at 5 g/kg body weight in rats.…”
Section: Introductionmentioning
confidence: 99%
“…Super Creatine™ (i.e. creatyl-L-leucine) is a novel ingredient consisting of creatine bound to L-leucine by a covalent bond and an initial toxicological evaluation in rodents demonstrated no genotoxic effects [33]. As this ingredient has never been independently evaluated as an ergogenic aid, it is impossible to determine to what extent it may have contributed to the beneficial effects of BMB.…”
Section: Discussionmentioning
confidence: 99%
“…As we are interested in the safety profile of MLE at higher doses, investigation utilizing internationally recognized guidelines, and the determination of a NOAEL for MLE, we submit herein the first in vitro and in vivo toxicological assessment of a mango leaf extract containing 60% MGF (MLE) conducted in accordance with the Organization of Economic Cooperation and Development (OECD) Principles of Good Laboratory Practices (GLP), ENV/MC/CHEM(98)17 [11], and the respective OECD guidelines. As the authors frequently perform this battery of toxicology studies, the methods description partly reproduces wording from other works [1214].…”
Section: Introductionmentioning
confidence: 99%